The Essence of Tafsir Fi Zilal al-Qurân and its Underlying Cultural-Linguistic and Dynamic Methods - Amir, Ahmad Nabil; Rahman, Tasnim Abdul (UIN Sunan Gunung Djati Bandung, 2025)
The paper aims to identify the essential methodology adopted by Sayyid Qutb in his classic work, tafsir Fi Zilal al-Qur’an. The work laid out highly profound interpretation and scriptural analysis of the Qur’an and its universal moral and political ideas based on cultural-linguistics and dynamic framework. The work set forth to expound socio-ethical principle of the Qur’an and its ideological postulate and implication in contemporary perspective. The study is based on qualitative approaches in the form of library and documentary survey. The data were obtained from related primary and secondary sources and analysed using descriptive, historical and analytical approaches. The finding shows that Sayyid Qutb had formulated an inclusive method of philosophical interpretation of the Qur’an that outlined his dynamic framework (haraki) of religious and ethico-legal views as its core ideological basis and premises. The pattern of thought and interpretation were influenced by this method in the development of his tafsir which underline his socio-political doctrine and philosophy and idealism which highlighted the essence of Islam and its underlying values in contemporary civilization.